2021
DOI: 10.3389/feart.2021.664673
|View full text |Cite
|
Sign up to set email alerts
|

Revealing 60 years of Earthquake Swarms in the Southern Red Sea, Afar and the Gulf of Aden

Abstract: Earthquake swarms occur sporadically at divergent plate boundaries but their recurrence over multiple decades and relation to magmatic spreading activity remain poorly understood. Here we study more than 100 earthquake swarms over a 60-year period in the southern Red Sea, Afar, and Gulf of Aden region. We first compiled an earthquake-swarm catalogue by integrating reexamined global and local earthquake catalogues from 1960 to 2017. This yielded 134 earthquake swarms that mainly cluster in 19 different areas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…Yellow lines are faults in the area of the 2022 sequence, orange dashed lines are fractures reported by Ruch et al. (2021). (c–e) wrapped co‐seismic interferograms for the initial part (c), later (d) part, and entire (e, f) seismic sequence.…”
Section: Introductionmentioning
confidence: 82%
“…Yellow lines are faults in the area of the 2022 sequence, orange dashed lines are fractures reported by Ruch et al. (2021). (c–e) wrapped co‐seismic interferograms for the initial part (c), later (d) part, and entire (e, f) seismic sequence.…”
Section: Introductionmentioning
confidence: 82%
“…Another very unusual aspect concerns the reported focal mechanisms. Thrust mechanisms are rarely reported at MOR (Ruch et al., 2021), where such failure type is incompatible with the dominant extensional stresses. The observation of large off rift thrust earthquakes during the 2022 is quite unique, likely requiring specific conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Strike‐slip mechanisms with rupture planes oblique to the ridge axis, instead, can be triggered at the tip of migrating dikes and provide evidence for a magmatic driver (Hill, 1977; Passarelli et al., 2015). Finally, thrust mechanisms have been rarely reported in extensional domains (Ruch et al., 2021; Wolfe et al., 2012) and require a strong perturbation of the background, tectonic stress.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this assumption may not be an overinterpretation. Recent studies have shown that below the southern Red Sea, there is ongoing magmatic activity creating local earthquake swarms [63,64]. However, we would like to emphasize the need for further studies (e.g., tomographic imaging) to unequivocally infer the origin of seismicity in the Abu-Dabbab area.…”
Section: Origin Of Seismicitymentioning
confidence: 93%